Photorefractive keratectomy, another choice for refractive surgery - Ausayakhun, Somsanguan; Supalaset, Sumet (Biomedical Sciences and Clinical Medicine, 2016)
PRK (Photorefractive Keratectomy) is a refractive surgery by removing the corneal epithelium and then using an excimer laser to reshape the corneal curvature, without corneal flap creation like LASIK. This review summarizes the advantages and the disadvantages of PRK when compare to LASIK, and also how to prepare for the PRK.